Metadatos Dublin Core y Protocolo OAI – PMH como tecnología semántica para la visibilidad de los recursos de la plataforma científica ECUCIENCIA - Quinatoa Arequipa, Edwin Edison (2023)
The Researcher professor at the Technical University of Cotopaxi requires that his research work be easy to access and view for people who require it and whose work is hosted on the Ecuciencia scientific platform, for which he proposed a metadata management system. using free software tools; For this, it was determined that there were already investigations but they did not allow the collection, filtering and processing of information, which caused the response to what was required not to be found, therefore, as the University is focused on computerizing all processes, the collection of information was generated by applying methodologies, tools and techniques such as Interviews with the coordinator of the scientific platform, in addition, Python programming tools and languages, PostgreSQL Database, Dublin Core metadata and OAI-PMH Protocol were used and Agile Practices were used to manage the application and to validate the functionalities, different test cases were used, which allowed us to obtain as a result an application that allows generating an optimal data harvester for the platform, which supports locating and recovering digital objects from the Institution's repository, and it is concluded that this will allow us to guarantee The reliability and ease of searching for information specifically on articles allows teachers, students and the general public to benefit from generating optimal research.